2007
DOI: 10.1111/j.1475-6773.2007.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Savings from the Prevention of Unintended Pregnancy: A Cost Analysis of Family Planning Services in California

Abstract: Objective. To assess the short-term economic savings associated with the prevention of unintended pregnancies through California's Medicaid family planning demonstration project. Data Sources. Secondary data from health and social service programs available to pregnant or parenting women at or below 200 percent of the federal poverty level in California in 2002 and data on the quantity and type of contraceptives dispensed to clients of California's 1115 Federal Medicaid demonstration project. Study Design. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 8 publications
0
59
0
Order By: Relevance
“…Of the eleven studies reviewed, five were conducted as state-specific analyses [7][8][9][10][11] , four as cross-state comparisons 12-15 and two examined aggregated national-level data 16,17 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the eleven studies reviewed, five were conducted as state-specific analyses [7][8][9][10][11] , four as cross-state comparisons 12-15 and two examined aggregated national-level data 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported on improvements in birth outcomes in response to publicly financed family planning care, citing a reduced number of low-birth weight births, births with late or no prenatal care, infant deaths and neonatal dates 14 . The most commonly reported measure across reviewed studies was unintended pregnancies averted [7][8][9][10]16,17 . When taken together, results from these state and national-level analyses suggest that publicly funded family planning services avert a significant proportion of unintended pregnancies.…”
Section: Study Design and Qualitymentioning
confidence: 99%
See 3 more Smart Citations